2011
DOI: 10.1111/j.1462-2920.2011.02677.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of copper surface toxicity in Escherichia coli O157:H7 and Salmonella involves immediate membrane depolarization followed by slower rate of DNA destruction which differs from that observed for Gram‐positive bacteria

Abstract: We have reported previously that copper I and II ionic species, and superoxide but not Fenton reaction generated hydroxyl radicals, are important in the killing mechanism of pathogenic enterococci on copper surfaces. In this new work we determined if the mechanism was the same in non-pathogenic ancestral (K12) and laboratory (DH5α) strains, and a pathogenic strain (O157), of Escherichia coli. The pathogenic strain exhibited prolonged survival on stainless steel surfaces compared with the other E. coli strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
169
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(180 citation statements)
references
References 65 publications
(124 reference statements)
4
169
1
1
Order By: Relevance
“…3B and D). It has been shown that generation of highly toxic hydroxyl radicals via Fenton reaction between Cu(I) and hydrogen peroxide combined with direct copper ion action led to the rapid death of Gram-negative bacteria on copper surfaces (20). The results from this new study suggest that reactive oxygen species (ROS) are involved in bacterial killing on copper but not via Fenton chemistry.…”
Section: Resultsmentioning
confidence: 57%
“…3B and D). It has been shown that generation of highly toxic hydroxyl radicals via Fenton reaction between Cu(I) and hydrogen peroxide combined with direct copper ion action led to the rapid death of Gram-negative bacteria on copper surfaces (20). The results from this new study suggest that reactive oxygen species (ROS) are involved in bacterial killing on copper but not via Fenton chemistry.…”
Section: Resultsmentioning
confidence: 57%
“…Reports have indicated that, in Gram-positive bacteria, the metal binding sites usually lie within the peptidoglycan layer (88,89). Copper also tends to accumulate on the inner side of the cell membrane, making the inner side more positive and, thus, causing membrane depolarization (11,90). Here, we demonstrated the effect of copper on initiating an immediate membrane potential dissipation, which was significantly higher in the ⌬copYAZ strain than in the wild-type strain.…”
Section: Discussionmentioning
confidence: 59%
“…In E. coli and Salmonella, contact killing on copper surfaces involves immediate membrane depolarization, leading to compromised cell viability (11). To test whether copper and CopYAZ modulate the membrane potential of S. mutans, we conducted fluorometric assays with bis-oxonol dyes, which can enter depolarized cells and bind intracellular proteins or membranes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years considerable progress has been made towards elucidating the bactericidal mechanism of copper [21][22][23][24][25][26][27]. There is no need to discuss it here, 1 other than to remark that the release of copper ions from the surface is required, hence the encapsulation matrix should be chosen so as to allow their (slow) release.…”
Section: Disastrous Performance Of Nanocote/aqua Based Antimicrobial mentioning
confidence: 99%